Investigations on a predictive process parameter adaptation for machining of hybrid workpieces. (November 2018) - Denkena, Berend; Bergmann, Benjamin; Witt, Matthias
Abstract: A new design concept for high-performance components involves the combination of different materials in workpiece compounds. This paper examines a predictive process parameter adaptation (PPPA) for the machining of friction welded EN‐AW6082/20MnCr5 shafts. The influences of the different material properties on the process forces and the shaft geometry were investigated. The machined material was identified by monitoring the material specific cutting force. The system latency of the components was modeled and used to define the starting position for the process parameter adaptation. To this end, the reaction time, delay time and mechanical adaptation time of the axes were determined and the inaccuracy of the model was discussed. A longitudinal turning process was performed with activated PPPA. The maximum tool load was successfully limited and the geometry error of the shaft diameter was reduced by approximately 90%.